Poverty Impacts of Improved Agricultural Productivity: Opportunities for Genetically Modified Crops - Ivanic, Maros; Martin, Will (2012)
Constraints on land and water resources, growth in population, and an apparent slowdown in agricultural productivity raise concerns that food prices may rise substantially in the coming decades. A key question is whether policies aimed at increasing agricultural productivity may be effective in reversing the long-run trend and bringing about significant reductions in food prices. This article uses a global general equilibrium model and a set of microeconomic household models for a sample of 26 developing countries to assess potential implications of higher agricultural productivity--such as through the adoption of genetically modified plants--for household incomes, farmer profits, and poverty. Higher agricultural productivity resulting from increased investments in research and development is found capable of significantly lowering poverty by lowering the cost of consumption of the poorest households without significantly hurting farmers' returns. We also found that raising agricultural productivity among the developing countries only is sufficient to achieve most poverty reduction in the global scenario.